Equity, Diversity, Inclusion, and Belonging in Canadian Music Therapy - Elizabeth Mitchell; Priya Zalis; Daniel Arun Robinson; Sarah Bell; Cynthia Bruce (Voices, 2025)
Issues of equity, diversity, inclusion, and belonging (EDIB) are urgent priorities for an increasing number of minoritized and allied music therapists. With the aim of addressing gaps in the current music therapy literature and inspired by the British Association for Music Therapy’s 2020 Diversity Report, the research team developed a questionnaire that was distributed to all Certified Music Therapists in Canada. This questionnaire asked for demographic data in addition to exploring Canadian music therapists’ perspectives, priorities, and concerns regarding EDIB within the professional landscape. This paper explores participants’ answers to three qualitative questions, where results from data analysis are delineated by three overarching themes: Power and Representation, The Role of Music, and Advocacy. We share our perspectives on key findings from the data analysis and connect our discussion to broader discourse surrounding systemic inequalities in healthcare, music practices, and society from our perspectives as minoritized and allied Canadian music therapists. We present ideas for future research and explore how our findings contribute to vital dialogue that challenges inequality, removes barriers, and supports progress toward becoming an inclusive profession that fosters belonging and represents the communities we serve.